2016
DOI: 10.1111/trf.13574
|View full text |Cite
|
Sign up to set email alerts
|

Blood graft cellular composition and posttransplant outcomes in myeloma patients mobilized with or without low‐dose cyclophosphamide: a randomized comparison

Abstract: CY plus G-GSF yields more CD34+ cells but seems to diminish lymphocyte and NK cell counts in the grafts and hampers immune recovery after transplantation. Thus G-CSF alone might be a preferred mobilization method due to more rapid immune recovery posttransplant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…We observed a significantly higher number of late granulocyte and monocyte forming myeloid progenitors in grafts collected in the CGP‐group whereas GP mobilized patients collected more CD19 + B‐cells and NK cells. Except for CD19 + B‐cells our results are comparable to other reports . The higher amount of late granulocyte precursors in grafts obtained after chemotherapy and plerixafor mobilization could lead to a more rapid ANC engraftment in these patients.…”
Section: Discussionsupporting
confidence: 87%
“…We observed a significantly higher number of late granulocyte and monocyte forming myeloid progenitors in grafts collected in the CGP‐group whereas GP mobilized patients collected more CD19 + B‐cells and NK cells. Except for CD19 + B‐cells our results are comparable to other reports . The higher amount of late granulocyte precursors in grafts obtained after chemotherapy and plerixafor mobilization could lead to a more rapid ANC engraftment in these patients.…”
Section: Discussionsupporting
confidence: 87%
“…Most of the other authors did not provide information about gating strategies but also reported higher proportions of CD38-/CD341 cells after plerixafor compared to G-CSF alone. [8][9][10]12,13 In addition, Taubert and coworkers 14 found increased proportions of CD38-cells after plerixafor mobilization and reported higher CD133 mRNA levels in CD341/ALDH bright cells. Based on recent studies describing a revision of the hematopoietic tree, 15,16 we established a multicolor single-platform analysis to enumerate CD34 subtypes of stem cell grafts.…”
Section: Discussionmentioning
confidence: 98%
“…Subsequent reports showed similar results. However, none of these groups described their gating strategies or showed figures depicting how “CD38 dim ” “CD38 low ” or “CD38 negative ” cells had been defined . Various groups have developed the model of a hematopoietic tree, describing the differentiation from the earliest CD34+ MPPs to lineage‐committed CD34+ precursors giving rise to defined blood cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations